Polyester modification method - Rollick, Kevin L (2021)
The subject invention provides a means for modifying existing polyester polymers to optimize characteristics for solid state polymerization and for utilization in a wide array of specific applications. For instance, the modification technique of this invention may be used to adjust the melting point, crystallization temperature (either from the solid or on cooling from the melt), glass transition temperature, natural stretch ratio, barrier properties, melt strength, and/or solid state polymerization characteristic of the polyester. Application of the instant invention could result in a polymer with substantially different physical properties, potentially allowing its use in heretofore high cost, specialty applications. A further advantage of the invention is that recycled polymer may be modified to broaden its potential uses into more demanding higher performance applications.